ANALISIS EFEK BANCASSURANCE PADA EFISIENSI DAN PROFITABILITAS BANK - FADHILA PUTRI TANTA; DENY DWI HARTOMO (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2020)
Nowadays, banks in Indonesia are starting to aggressively issue new products, namely bancassurance. Bancassurance is a banking product obtained from the collaboration between a bank and an insurance company. From this collaboration, banks are expected to gain profitability and can improve their efficiency. Therefore, this research is intended to find out whetherbancassurance is able to provide efficiency and profitability to banks in Indonesia. This study took samples of banks listed on the Indonesia Stock Exchange in the period 2013-2017 with the purposive sampling method obtained a sample of 9 banks. The results of the analysis show thatbancassurance does not have a positive and significant effect on efficiency and also does not have a significant effect on profitability, but shows a positive impact on profitability. Keyword: bancassurance, efficiency, profitability